Single-cell transcriptome analysis uncovers underlying mechanisms of acute liver injury induced by tripterygium glycosides tablet in mice - Guo, Qiuyan; Wu, Jiangpeng; Wang, Qixin; Huang, Yuwen; Chen, Lin; Gong, Jie; Du, Maobo; Cheng, Guangqing; Lu, Tianming; Zhao, Minghong; Zhao, Yuan; Qiu, Chong; et al. (Journal of pharmaceutical analysis, 2023)
Tripterygium glycosides tablet (TGT), the classical commercial drug of Tripterygium wilfordii Hook. F. has been effectively used in the treatment of rheumatoid arthritis, nephrotic syndrome, leprosy, Behcet's syndrome, leprosy reaction and autoimmune hepatitis. However, due to its narrow and limited treatment window, TGT-induced organ toxicity (among which liver injury accounts for about 40% of clinical reports) has gained increasing attention. The present study aimed to clarify the cellular and molecular events underlying TGT-induced acute liver injury using single-cell RNA sequencing (scRNA-seq) technology. The TGT-induced acute liver injury mouse model was constructed through short-term TGT exposure and further verified by hematoxylin-eosin staining and liver function-related serum indicators, including alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and total bilirubin. Using the mouse model, we identified 15 specific subtypes of cells in the liver tissue, including endothelial cells, hepatocytes, cholangiocytes, and hepatic stellate cells. Further analysis indicated that TGT caused a significant inflammatory response in liver endothelial cells at different spatial locations; led to marked inflammatory response, apoptosis and fatty acid metabolism dysfunction in hepatocytes; activated hepatic stellate cells; brought about the activation, inflammation, and phagocytosis of liver capsular macrophages cells; resulted in immune dysfunction of liver lymphocytes; disturbed the intercellular crosstalk in liver microenvironment by regulating various signaling pathways. Thus, these findings elaborate the mechanism underlying TGT-induced acute liver injury, provide new insights into the safe and rational applications in the clinic, and complement the identification of new biomarkers and therapeutic targets for liver protection. [Display omitted] •TGT induced acute liver injury via the regulation of inflammatory response.•TGT treatment resulted in hepatocyte apoptosis and HSC activation.•TGT treatment caused activated LCM cells and the immune dysfunction of lymphocyte.